Ensino de ciências no 5º ano do ensino fundamental: o currículo modelado e aspectos do currículo em ação - Dourado, Sandra Maria de Araújo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This study aims to investigate the science teaching in the early years of elementary school, analyzing the curriculum modeled by teachers and instances of it being used, taking as reference the procedural approach of the Gimeno Sacristán curriculum. A qualitative research was conducted through analysis of official documents and materials produced by teachers and students of the 5th year of elementary school from two public schools in Araraquara, São Paulo State, Brazil. The documents analyzed were: the annual plan and weekly routines produced by teachers of one class at each school, the class plan of one student from each of the classes, and the textbook used in schools. These documents were compared with the curriculum requirements in Federal level − the National Curriculum Parameters of Natural Sciences for the Early Years − and State level − the Learning Expectations: Cycle I, from the State Department of Education. The annual plans, the weekly routines and the class plans enabled us to identify that teachers select part of the contents and the learning expectations within the official documents, with differences in teachers' choices in the two schools. In addition, through notes in the students' notebooks, we see that the textbook is used significantly, with almost complete reproduction of excerpts from the material. Still, the selected activities are those that prioritize conceptual contents, to the detriment of proposals with an investigative approach or of procedural and attitudinal contents covered by the books. The analysis of the results allows us to see the active and decisive role of the teachers in the implementation of content from textbooks, acting as translators of the given curriculum and the curriculum presented to them

O trabalho tem como objetivo investigar o ensino de Ciências nos anos iniciais do Ensino Fundamental, analisando o currículo modelado pelos professores e indícios do currículo em ação, tomando-se como referencial teórico a abordagem processual de currículo de Gimeno Sacristán. Foi realizada uma pesquisa qualitativa, por meio de análise de documentos oficiais e de materiais produzidos por professores e alunos do 5º ano do Ensino Fundamental de duas escolas públicas de Araraquara − SP. Os documentos analisados foram: o plano anual e as rotinas semanais produzidos pelos professores de uma turma de cada escola, o caderno de classe de um aluno de cada escola e o livro didático adotado nas escolas. Tais documentos foram comparados com as prescrições curriculares em nível federal − os Parâmetros Curriculares Nacionais de Ciências Naturais para os Anos Iniciais e estadual − as Expectativas de Aprendizagem - Ciclo I, da Secretaria do Estado da Educação de São Paulo. Os planos anuais, as rotinas semanais e os cadernos possibilitaram identificar que os professores selecionam parte dos conteúdos e expectativas de aprendizagem presentes nos documentos oficiais, havendo diferenças nas escolhas dos professores das duas escolas. Além disso, pelas anotações nos cadernos dos alunos, verificamos que o livro didático é utilizado de forma expressiva, com reprodução quase integral de trechos desse material. Ainda assim, as atividades selecionadas são as que priorizam conteúdos conceituais, em detrimento de propostas com abordagem investigativa ou de conteúdos procedimentais e atitudinais explorados pelos livros. A análise dos resultados permite perceber o papel ativo e decisivo do professor na concretização dos conteúdos de sua prática, atuando como tradutor do currículo prescrito e do currículo que lhe é apresentado
Keywords: Educação; Ensino; Ensino fundamental; Ciências ambientais - Estudo e ensino; Education